Programmatic management of drug-resistant tuberculosis financing in Lampung Province - Utomo, Siti Syamsiyyah Nurmalisa; Hafidz, Firdaus; Dewi, Christa (BKM Public Health and Community Medicine, 2022)
Purpose: This research aims to get an overview of Programmatic Management of Drug-Resistant Tuberculosis (PMDT) Financing in Lampung in 2021. Methods: This is a mixed-methods research study aimed at determining the amount of financing for PMDT from a payer perspective and assessing the local government's commitment. Financing calculation using Lampung Provincial Health Office, Global Fund, and BPJS Kesehatan financial data. The local government's commitment was evaluated by a focus group discussion with the Lampung Provincial Health Office officer. Results: The total financing for the PMDT in 2021 was Rp 6,072,456,520, with 92.12% of funding sources coming from donors, 6.17% from APBN, 1.71% from JKN, and 0% from the APBD. The activities with the highest costs are the provision of anti-tuberculosis drugs at 35% and additional logistics at 34%. Conclusion: The main challenge in financing PMDT is the high-cost requirement, which the local fiscal capacity doesn't support. It should be an essential concern for local governments to ensure the program's sustainability after the termination of Global Fund funding. The government must enhance local fiscal capacity in the post-pandemic era and promptly develop and implement a national health insurance scheme to finance PMDT.